Amido Silicon Chalcogenide Compounds with Unprecedented Cluster Cores and Low Oxidation State Silicon Atoms. Issue 44 (20th November 2019) - Schwedtmann, Kevin; Hepp, Alexander; Schwedtmann, Kai; Weigand, Jan J.; Lips, Felicitas
Abstract: Invited for the cover of this issue is Felicitas Lips from the University of Münster, Germany. The cover image shows butterflies trapped in a series of silicon‐based cages. The color of each cage compound is represented by the color of the butterfly in it. Abstract : The most exciting aspect was the discovery that two selenides with different cluster cores, that is, a nortricyclane‐type cage and a tricycloheptane‐type cage, both isomerize to form a new compound with a defect‐hetero‐cubane‐type cage … Read more about the story behind the cover in the Cover Profile and about the research itself in the Full Paper by F. Lips et al.